1996
DOI: 10.1021/ci950360j
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Conserved Residues between Halobacterial Retinal Proteins and G-Protein Coupled Receptors:  Implications for GPCR Modeling

Abstract: An alignment of the transmembrane domains of halobacterial retinal proteins (including bacteriorhodopsin) and G-protein coupled receptors (GPCRs) is presented based on the commonality of conserved residues between families. Due to the limited sequence homology displayed by these proteins, an alternative strategy is proposed for sequence alignment that correlates residues within secondary structure elements. The nonsequential alignment developed identifies three proline and two aspartates residues that share co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…60 In both her models, she incorporated an analysis of interhelical loop lengths and analyses of residue conservation, variability, and polarity. Among her conclusions, she demonstrated that the helices almost certainly had to be arranged adjacent to each other; atypical arrangements such as those by Pardo 61 and Metzger et al 62 are shown to be fairly unlikely. Furthermore, although her analysis was consistent with either a clockwise or counterclockwise arrangement of helices, she determined that the latter was more likely.…”
Section: G-protein Coupled Receptorsmentioning
confidence: 90%
“…60 In both her models, she incorporated an analysis of interhelical loop lengths and analyses of residue conservation, variability, and polarity. Among her conclusions, she demonstrated that the helices almost certainly had to be arranged adjacent to each other; atypical arrangements such as those by Pardo 61 and Metzger et al 62 are shown to be fairly unlikely. Furthermore, although her analysis was consistent with either a clockwise or counterclockwise arrangement of helices, she determined that the latter was more likely.…”
Section: G-protein Coupled Receptorsmentioning
confidence: 90%
“…Computations were performed using a constant dielectric of 4 with a nonbonded cutoff distance of 8.0 Å. The initial coordinates of the TM region of the κ-receptor were taken from a model previously developed in our group to rationalize the binding of naltrexone-based ligands. , This model is unique in that secondary structures are taken from nonsequential alignments to the helical domains of bacteriorhodopsin (BR) …”
Section: Methodsmentioning
confidence: 99%
“…The initial coordinates of the TM region of the κ-receptor were taken from a model previously developed in our group to rationalize the binding of naltrexone-based ligands. 2,21 This model is unique in that secondary structures are taken from nonsequential alignments to the helical domains of bacteriorhodopsin (BR). 21 This allows the conformational effects of the conserved prolines to be retained in the opioid model which is not possible through direct sequence alignment to BR.…”
Section: Methodsmentioning
confidence: 99%
“…48 When these four residues are engineered FIGURE 2 Ribbon picture of the transmembrane domains of the GPCRs. The generation of the ribbon model of the GPCR and the coordinate used are described in Metzger et al 138 into the opioid receptor, the resultant opioid receptor mutant can bind DAMGO with high affinity and can efficiently inhibit adenylyl cyclase in response to the agonist. The same mutant did not exhibit high affinity for other opioid receptor peptidic ligands such as dermorphin, CTOP, or Met 5 -enkephalin, or nonpeptidic ligands such as morphine, methadone, or fentanyl.…”
Section: Involvement Of Extracellular Loops In Ligand Recognition Andmentioning
confidence: 99%